The impact of enteral feeding and therapeutic monitoring of rifampicin with dose escalation in critically ill patients with tuberculosis. (January 2023) - Perumal, Rubeshan; Naidoo, Kogieleum; Naidoo, Anushka; Letsoalo, Marothi P.; Esmail, Aliasgar; Joubert, Ivan; Denti, Paolo; Wiesner, Lubbe; Padayatchi, Nesri; Maartens, Gary; Dheda, Keertan
Highlights: Rifampicin concentrations were low in all continuously fed critically ill patients. Dose escalation increased drug exposure and achieved target concentrations. Therapeutic drug monitoring should be implemented in critically ill patients to improve dose optimization. Further research is required to determine the impact of therapeutic drug monitoring on clinical outcomes. Abstract: Objectives: Critically ill patients with tuberculosis (TB) face a high mortality risk and require effective treatment. There is a paucity of data on rifampicin pharmacokinetics, the impact of continuous enteral feeding on drug absorption, and the potential of therapeutic drug monitoring (TDM) to optimize drug exposure in these patients. Methods: We performed a sequential pharmacokinetic study to determine the impact of feeding and TDM with rifampicin dose escalation in critically ill patients with TB. Noncompartmental pharmacokinetic analysis was performed. Results: Among 20 critically ill patients (40% were HIV-infected), median rifampicin Cmax (maximum serum concentration) in the fasted and fed states were 5.1 µg/ml versus 3.3 µg/ml, respectively ( P <0.0001; geometric mean ratio 1.95; 90% confidence interval 1.46-2.60). The proportion of patients with low rifampicin concentrations in the fasted and fed states was 80% vs 100% ( P -value = 0.1336). Optimized dosing led to a per-patient median rifampicin dosing of 24.6 mg/kg and a median Cmax increase from 2.4 µg/ml to 17.8 µg/ml ( P -value = 0.0005; geometric mean ratio 8.29; 90% confidence interval 3.88-17.74). TDM-guided dose escalation increased the proportion of patients achieving the suggested target rifampicin concentration compared with standard dosing (83% vs 0%, P -value = 0.004). Conclusion: We found low rifampicin concentrations in all patients receiving continuous enteral feeding. TDM-guided dose escalation provided an effective strategy to achieve target drug exposure in these critically ill patients with TB.